State-of-the-art diagnosis of autoimmune blistering diseases - van Beek, Nina; Holtsche, Maike M.; Atefi, Ingeborg; Olbrich, Henning; Schmitz, Marie J.; Pruessmann, Jasper; Vorobyev, Artem; Schmidt, Enno (Frontiers in Immunology, 2024)
Autoimmune blistering disorders (AIBD) are a heterogenous group of about a dozen entities comprising pemphigus and pemphigoid disorders and dermatitis herpetiformis. Exact diagnosis of AIBD is critical for both prognosis and treatment and is based on the clinical appearance combined with the detection of tissue-bound and circulating autoantibodies. While blisters and erosions on the skin and/or inspectable mucosal surfaces are typical, lesions may be highly variable with erythematous, urticarial, prurigo-like or eczematous manifestations. While direct immunofluorescence microscopy (IFM) of a perilesional biopsy is still the diagnostic gold standard, the molecular identification of the major target antigens opened novel therapeutic avenues. At present, most AIBD can be diagnosed by the detection of autoantigen-specific serum antibodies by ELISA or indirect IFM when the clinical picture is known. This is achieved by easily available and highly specific and sensitive assays employing recombinant immunodominant fragments of the major target antigens, i.e. desmoglein 1 (for pemphigus foliaceus), desmoglein 3 (for pemphigus vulgaris), envoplakin (for paraneoplastic pemphigus), BP180/ type XVII collagen (for bullous pemphigoid, pemphigoid gestationis, mucous membrane pemphigoid), laminin 332 (for mucous membrane pemphigoid), laminin 4 (for anti-p200 pemphigoid), type VII collagen (for epidermolysis bullosa acquisita and mucous membrane pemphigoid), and transglutaminase 3 (for dermatitis herpetiformis). Indirect IFM on tissue substrates and in-house ELISA and immunoblot tests are required to detect autoantibodies in some AIBD patients including those with linear IgA disease. Here, a straight forward modern approach to diagnose AIBD is presented including diagnostic criteria according to national and international guidelines supplemented by long-term in-house expertise.